Recent Progress and Future Prospective in HBV Cure by CRISPR/Cas - Yu-Chan Yang; Hung-Chih Yang (Viruses, 2021)
Hepatitis B virus (HBV) infection remains an important issue of global public health. Although current antiviral therapy has dramatically reduced the mortality and morbidity of chronic hepatitis B (CHB), it fails to cure it. Rebound viremia often occurs after stopping antiviral therapy. Persistent HBV covalently closed circular DNA (cccDNA) and integrated DNA under antiviral therapy form the major barrier to eradication of HBV infection. CRISPR-mediated genome editing has emerged as a promising therapeutic approach to specifically destroy persistent HBV genomes, both cccDNA and integrated DNA, for HBV cure. However, the cleavage of integrated HBV DNA by CRISPR-Cas9 will cause double-strand break (DSB) of host genome, raising a serious safety concern about genome instability and carcinogenesis. The newly developed CRISPR-derived base editors (BEs), which fuse a catalytically disabled nuclease with a nucleobase deaminase enzyme, can be used to permanently inactivate HBV genome by introducing irreversible point mutations for generation of premature stop codons without DSBs of host genome. Although promising, CRISPR-mediated base editing still faces daunting challenges before its clinical application, including the base-editing efficacy, the off-target effect, the difficulty in finding conserved target HBV sequences, and in vivo delivery efficiency. Several strategies have been adopted to optimize the efficiency and specificity of CRISPR-BEs and to improve in vivo delivery efficacy through novel viral and non-viral delivery approaches. Particularly, the non-viral delivery of Cas9 mRNA and ribonucleoprotein by lipid nanoparticles exhibits attractive potential for liver-targeted delivery in clinical. Along with all progress above, the CRISPR-mediated gene therapy will ultimately achieve HBV cure.